Vertical distribution of epiphyton biomass and diversity in a shallow lake during contrasting ecosystem regimes - Cano, Maria Gabriela (2013)
We investigated seasonal and depth variations in biomass and composition of bulrush-associated epiphyton in a shallow seepage lake in Argentina and examined whether differences existed in the vertical profiles between sites, whether the zonation with respect to depth changed according to different regimes of the ecosystem, and what conditions most greatly affected the epiphyton vertical distribution. We performed sample collection every 4 weeks for one year at both the centre and the periphery of the bulrush stand, sectioned the bulrush stems into segments to give a fixed 7-level vertical profile, and recorded the water physicochemical characteristics over the same profile. The epiphyton vertical variations were similar at both sampling locations.The epiphyton-biomass profiles underwent an abrupt change at a depth of 45-65. cm during the clear-water period, while comparable values were recorded along the profiles during the turbid phase. The temperature had a positive effect during late spring-early summer that coincided with the transitional period and beginning of the clear period.The principal driver of the epiphyton-biomass vertical distribution is the light availability, followed by the exposure to water movements. The resident species with high contributions to the overall biovolume were related to the percentage of incident light, and particularly those community members that were predominant in the clear-water period.